Analisa Kinerja Lemari Pendingin Alami Sebagai Penyimpan Sayur dan Buah-buahan dengan Media Pendingin Air - Sitorus, Tulus Burhanuddin; Sitepu, Tekad (Sanata Dharma University, 2016)
One application of direct evaporation cooling system was a natural refrigerator. The advantages of this natural refrigerator was operating without using electrical energy or mechanical energy and environmentally friendly. This study aims to gain a performance analysis of natural refrigerator as a store of vegetables and fruits which uses water as the cooling medium. Material of natural refrigerator consists of teak wood and gunny. Experiments were conducted during seven days in the open space which exposure to solar radiation. The measurement of weather parameterÂ was done by using HOBO devices and to record temperature changes of vegetables and fruits in the natural refrigerator was used acquisition data. The results showed that the efficiency of natural refrigerator maximum that can be obtained was 14.7% with an average air temperature of 25,55oC, air humidity average of 91.34% and an average solar radiation of 108.45 W/m2. The experimental data showed that the freshness of vegetables and fruits heavily influenced by weather conditions.